2009
DOI: 10.1182/blood-2008-08-175653
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1/2 study of fractionated 131I-rituximab in low-grade B-cell lymphoma: the effect of prior rituximab dosing and tumor burden on subsequent radioimmunotherapy

Abstract: The effect of induction therapy with multiple doses of rituximab on the subsequent efficacy and toxicity of anti-CD20 radioimmunotherapy is unknown. We evaluated a novel protocol using 4 weekly infusions of 375 mg/m 2 rituximab followed by 2 fractions of 131 I-rituximab, preceded by a 100-mg/m 2 predose of rituximab, in relapsed indolent B-cell lymphoma. Induction therapy with rituximab significantly increased the effective half-life of 131 I-rituximab (P ‫؍‬ .003) and high serum levels of rituximab after indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 40 publications
(41 reference statements)
3
42
2
Order By: Relevance
“…31 After infusion of 375 mg/m 2 rituximab, a more favorable biodistribution with selective tumor targeting of 131 I-rituximab at sites of nodal disease was seen. 31 In vitro studies imply that the sequential use of anti-CD20 mAb may result in the inhibition of binding of the second anti-CD20 mAb, 32 but prior rituximab did not adversely affect the response to 131 I-rituximab in a phase 2 clinical study, 7 compared with rituximabnaïve patients. Whether the pre-RIT rituximab dose affects the response to RIT in vivo has not been conclusively demonstrated, but recent studies suggest an enhanced efficacy.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…31 After infusion of 375 mg/m 2 rituximab, a more favorable biodistribution with selective tumor targeting of 131 I-rituximab at sites of nodal disease was seen. 31 In vitro studies imply that the sequential use of anti-CD20 mAb may result in the inhibition of binding of the second anti-CD20 mAb, 32 but prior rituximab did not adversely affect the response to 131 I-rituximab in a phase 2 clinical study, 7 compared with rituximabnaïve patients. Whether the pre-RIT rituximab dose affects the response to RIT in vivo has not been conclusively demonstrated, but recent studies suggest an enhanced efficacy.…”
mentioning
confidence: 96%
“…Whether the pre-RIT rituximab dose affects the response to RIT in vivo has not been conclusively demonstrated, but recent studies suggest an enhanced efficacy. 31 Induction therapy with high-dose rituximab administered before 131 I-rituximab RIT increased the effective circulating half-life from 45 to more than 90 hours. 31 Induction therapy did not appear to compromise the clinical effects of RIT with 131 I-rituximab or increase myelotoxicity.…”
mentioning
confidence: 99%
“…We found that induction therapy with rituximab significantly increases the effective half-life of subsequent 131 I-rituximab and correlated with increased effective half-life of the 131 I-rituximab. 7 Importantly, we demonstrated that multiple doses of rituximab did not appear to compromise the clinical efficacy or increase the myelotoxicity of subsequent anti-CD20 targeted RIT.…”
Section: Rituximab Perhaps These Important Questions Must Ultimatelymentioning
confidence: 95%
“…However decreased targeting leading to decreased efficacy of RIT has not thus far been observed in the clinic and if there is a deleterious effect with large amounts of mAb predosing, this does not appear to substantially affect the clinical efficacy. 7 Perhaps of greater concern in improving outcomes for patients with follicular lymphoma is the gross under usage of RIT. In an era where immunochemotherapy has substantially improved outcome, it is perhaps easier to become complacent that using such an effective treatment is not required in the treatment algorithm of follicular lymphoma.…”
Section: Rituximab Perhaps These Important Questions Must Ultimatelymentioning
confidence: 99%
“…Also, neither clinical efficacy of RIT did appear to be compromised, nor toxicity increased. 20 Similarly, in 2 trials using rituximab + chemotherapy combination therapy before 90 Y-IT application, 28,29 a significant rate of conversion from partial response (PR) to complete response (CR) was observed, again indicating that prior rituximab therapy does not hamper RIT. Since 2002, 90 Y-IT is approved in the United States (US) for patients with CD20+FL or transformed B-cell NHL, refractory to or relapsed after rituximab.…”
Section: Dovepressmentioning
confidence: 99%